2019
DOI: 10.1002/eat.23008
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of indirect effects of personality features on anorexia nervosa severity through interoceptive dysfunction in individuals with lifetime anorexia nervosa diagnoses

Abstract: Objective: This study examined a hypothesized pathway by which interoceptive dysfunction accounted for associations between personality features (harm avoidance, self-directedness, and perfectionism) and anorexia nervosa (AN) severity (indicated by drive for thinness, eating disorder-related preoccupations and rituals, and body mass index).Method: The study sample (n = 270, mean age = 28.47, 95.2% female, 98% White/Caucasian) consisted of probands and biological relatives who met DSM-IV criteria for lifetime d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
(47 reference statements)
4
9
0
Order By: Relevance
“…In line with previous literature findings, our AN patients presented a lower mood baseline and a higher EMSs score compared with HCs (Damiano et al, ; Meehan, Loeb, Roberto, & Attia, ). This is consistent with previous literature that showed how AN patients present a specific temperamental, cognitive, and behavioural profile with a rigid approach to changes that can affect a mild, flexible mind state as well as their connection with feelings and emotions (Duffy et al, ; Kaye et al, ; Oldershaw, Startup, & Lavender, ; Steinglass & Foerde, ). The literature has already shown that the AN patients present lower self‐esteem, higher fear of negative evaluation, and higher social physical comparison than controls, which are feelings that can affect social relationships (Cardi et al, ; Duarte, Ferreira, & Pinto‐Gouveia, ).…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous literature findings, our AN patients presented a lower mood baseline and a higher EMSs score compared with HCs (Damiano et al, ; Meehan, Loeb, Roberto, & Attia, ). This is consistent with previous literature that showed how AN patients present a specific temperamental, cognitive, and behavioural profile with a rigid approach to changes that can affect a mild, flexible mind state as well as their connection with feelings and emotions (Duffy et al, ; Kaye et al, ; Oldershaw, Startup, & Lavender, ; Steinglass & Foerde, ). The literature has already shown that the AN patients present lower self‐esteem, higher fear of negative evaluation, and higher social physical comparison than controls, which are feelings that can affect social relationships (Cardi et al, ; Duarte, Ferreira, & Pinto‐Gouveia, ).…”
Section: Discussionsupporting
confidence: 92%
“…A novel feature of the present work was the association of symptom deterioration with low levels of self‐directedness. This aligns with other work in confinement Moccia et al (2020) and to the extensive literature associating in ED lower self‐directedness to poorer prognosis (Duffy et al, 2019; Krug et al, 2011). Age and ED severity, named drive for thinness (EDI‐2), were also related with COVID‐19 concerns.…”
Section: Discussionsupporting
confidence: 91%
“…AN, anorexia nervosa; BED, binge eating disorder; BN, bulimia nervosa; OSFED, other specified feeding and eating disorder [Colour figure can be viewed at wileyonlinelibrary.com] directedness, in BN, were also found as predictors of therapy-response. These findings also align with previous literature (Amianto, Spalatro, Ottone, Abbate Daga, & Fassino, 2017;Duffy et al, 2019;Haynos et al, 2017Haynos et al, , 2018.…”
Section: Predictive Models Of Therapy Nonresponse and Drop-outsupporting
confidence: 93%